Patient Survival Between Hemodialysis and Peritoneal Dialysis Among End-Stage Renal Disease Patients Secondary to Myeloperoxidase-ANCA-Associated Vasculitis - Wu, Xueqin; Zhong, Yong; Meng, Ting; Ooi, Joshua Daniel; Eggenhuizen, Peter J.; Tang, Rong; Nie, Wannian; Xiao, Xiangcheng; Sun, Jian; Ao, Xiang; Zhang, Hao (Frontiers in Medicine, 2022)
Background A significant proportion of anti-neutrophil cytoplasmic antibody (ANCA) associated glomerulonephritis eventually progresses to end-stage renal disease (ESRD) thus requiring long-term dialysis. There is no consensus about which dialysis modality is more recommended for those patients with associated vasculitis (AAV-ESRD). The primary objective of this study was to compare patient survival in patients with AAV-ESRD treated with hemodialysis (HD) or peritoneal dialysis (PD). Methods This double-center retrospective cohort study included dialysis-dependent patients who were treated with HD or PD. Clinical data were collected under standard format. The Birmingham vasculitis activity score (BVAS) was used to evaluate disease activity at diagnosis and organ damage was assessed using the vasculitis damage index (VDI) at dialysis initiation. Results In total, 85 patients were included: 64 with hemodialysis and 21 with peritoneal dialysis. The patients with AAV-PD were much younger than the AAV-HD patients (48 vs. 62, P < 0.01) and more were female (76.2 vs. 51.6%, P = 0.05). The laboratory data were almost similar. The comorbidities, VDI score, and immuno-suppressive therapy at dialysis initiation were almost no statistical difference. Patient survival rates between HD and PD at 1 year were 65.3 vs. 90% (P = 0.062), 3 year were 59.6 vs. 90% (P < 0.001), and 5 years were 59.6 vs. 67.5% (P = 0.569). The overall survival was no significant difference between the two groups (P = 0.086) and the dialysis modality (HD or PD) was not shown to be an independent predictor for all-cause death (hazard ratio (HR) 0.73; 95% confidence interval (CI) 0.31–1.7; P = 0.473). Cardio-cerebrovascular events were the main cause of death among AAV-HD patients while infection in patients with AAV-PD. Conclusion These results provide real-world data that the use of either hemodialysis or peritoneal dialysis modality does not affect patient survival for patients with AAV-ESRD who need long-term dialysis.